Power flow control in parallel transmission lines based on UPFC - Mohammed Y. Suliman; Mahmood T. Al-Khayyat (Bulletin of Electrical Engineering and Informatics, 2020)
The power flow controlled in the electric power network is one of the main factors that affected the modern power systems development. The unified power flow controller (UPFC) is a FACTS powerful device that can control both active and reactive power flow of parallel transmission lines branches. In this paper, modelling and simulation of active and reactive power flow control in parallel transmission lines using UPFC with adaptive neuro-fuzzy logic is proposed. The mathematical model of UPFC in power flow is also proposed. The results show the ability of UPFC to control the flow of powers components "active and reactive power" in the controlled line and thus the overall power regulated between lines.